2022
DOI: 10.1093/eurjcn/zvac108
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a heart failure nurse practitioner service on rehospitalizations, emergency presentations, and survival in patients hospitalized with acute heart failure

Abstract: Aims Heart failure nurse practitioners (HF NP) are an emerging component of the heart failure (HF) specialist workforce but their impact in an inpatient setting is untested. The aim of this paper is to explore the impact of an inpatient HF NP service on 12 month all-cause rehospitalisations, emergency department (ED) presentations and mortality in patients hospitalised with HF compared to usual hospital care. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Both trials reported a reduced 30‐days readmission rate. In addition, there are two reports of retrospective two‐group comparisons with a total of fewer than 500 patients that also report reduced HF readmission in the nurse‐supported care group [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both trials reported a reduced 30‐days readmission rate. In addition, there are two reports of retrospective two‐group comparisons with a total of fewer than 500 patients that also report reduced HF readmission in the nurse‐supported care group [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%